Reassessing the climate change cooperation performance via a non-compensatory composite indicator approach. (10th April 2020) - Zhang, L.P.; Zhou, P.; Qiu, Y.Q.; Su, Q.; Tang, Y.L.
Abstract: International cooperation is the key factor in mitigating the climate change impacts on the human and environmental system. Climate change cooperation index can incentivize countries to embrace international agreements to achieve an efficient mitigation. This paper argues that non-compensatory rule can generate a more theoretically meaningful climate change cooperation index if the preferential independence between indicators cannot be guaranteed, sub-indicator weights are assigned with the meaning of the importance and compensability between sub-indicator is not desirable. Hence, this paper introduces a non-compensatory composite indicator approach to construct a new climate change cooperation index for cooperation performance evaluation. The main results are reported and discussed. An uncertainty analysis shows that the non-compensatory index has relatively good robustness on both weight factor and data inaccuracy. Highlights: Climate change cooperation index is constructed by a non-compensatory approach. The climate change cooperation performance for 161 countries is re-assessed. Uncertainty analysis is done to show the robustness of the evaluation results.